Molecular mechanisms underlying the clinical efficacy of panobinostat involve Stochasticity of epigenetic signaling, sensitization to anticancer drugs, and induction of cellular cell death related to cellular stresses - El Omari, Nasreddine; Bakrim, Saad; Khalid, Asaad; Abdalla, Ashraf N.; Almalki, Waleed Hassan; Lee, Learn-Han; Ardianto, Chrismawan; Long, Chiau Ming *; Bouyahya, Abdelhakim (Elsevier, 2023)
Panobinostat, also known as Farydak®, LBH589, PNB, or panobinostat lactate, is a hydroxamic acid that has been approved by the Food and Drug Administration (FDA) for its anti-cancer properties. This orally bioavailable drug is classified as a non-selective histone deacetylase inhibitor (pan-HDACi) that inhibits class I, II, and IV HDACs at nanomolar levels due to its significant histone modifications and epigenetic mechanisms. A mismatch between histone acetyltransferases (HATs) and HDACs can negatively affect the regulation of the genes concerned, which in turn can contribute to tumorigenesis. Indeed, panobinostat inhibits HDACs, potentially leading to acetylated histone accumulation, re-establishing normal gene expression in cancer cells, and helping to drive multiple signaling pathways. These pathways include induction of histone acetylation and cytotoxicity for the majority of tested cancer cell lines, increased levels of p21 cell cycle proteins, enhanced amounts of pro-apoptotic factors (such as caspase-3/7 activity and cleaved poly (ADP-ribose) polymerase (PARP)) associated with decreased levels of anti-apoptotic factors [B-cell lymphoma 2 (Bcl-2) and B-cell lymphoma-extra-large (Bcl-XL)], as well as regulation of immune response [upregulated programmed death-ligand 1 (PD-L1) and interferon gamma receptor 1 (IFN-γR1) expression] and other events. The therapeutic outcome of panobinostat is therefore mediated by sub-pathways involving proteasome and/or aggresome degradation, endoplasmic reticulum, cell cycle arrest, promotion of extrinsic and intrinsic processes of apoptosis, tumor microenvironment remodeling, and angiogenesis inhibition. In this investigation, we aimed to pinpoint the precise molecular mechanism underlying panobinostat's HDAC inhibitory effect. A more thorough understanding of these mechanisms will greatly advance our knowledge of cancer cell aberrations and, as a result, provide an opportunity for the discovery of significant new therapeutic perspectives through cancer therapeutics.